PTU-028 Balloon Sphincteroplasty after Sphincterotomy: A Safe Way to Ensure a British Society of Gastroenterology ERCP Target is Achieved. (17th August 2016) - Wolfson, P; Bouri, S; Sayers, R; Shariff, M; Macfarlane, B; King, A; Leahy, A
Abstract : Introduction: Sphincterotomy and balloon/basket trawl at ERCP is the standard treatment to clear stones from the common bile duct. The BSG in 2014 published a key performance indicator of >75% stone clearance during first ERCP. Balloon sphincteroplasty as an adjunct to sphincterotomy can increase stone clearance. The aim of this study is to review the success/safety for balloon sphincteroplasty compared to sphincterotomy alone. Methods: Retrospective study between 1 st April 2010–2014 in a large district general hospital of all ERCPs documenting a common bile duct stone. Electronic records were analysed with the following exclusion criteria: anticoagulants, biliary leak, unchecked cardiac device or incomplete follow up. Balloon sphincteroplasty was always performed after a sphincterotomy, using a Boston Scientific CRE wire guided balloon with a maximal diameter dilation that corresponded to the patient's mid common bile duct diameter (8–15 mm). Results: Total study population was 390 patients. Stone clearance with initial sphincterotomy alone and balloon/basket trawl was successful in 70% (n = 274) patients. 116 patients underwent additional balloon sphincteroplasty with a success rate of 85.5% (n = 100). The remaining patients underwent mechanical lithotripsy (n = 15) or tertiary care referral (n = 1). Therefore, sphincterotomy +/- balloon sphincteroplasty achieved stone clearance in 96% (n = 374) of patients. No statistically significant diferences were observed for complication rates when comparing sphincterotomy alone to balloon sphincteroplasty. Actual complication rates for sphincterotomy alone/balloon sphincteroplasty were: overall 5%/5.2%; pancreatitis 1%/2.6%; cholangitis 3%/3%; bleeding 3%/0% perforation 0%/0%. Conclusion: Balloon sphincteroplasty is an effective and safe adjunct in patients who do not achieve bile duct stone clearance with sphincterotomy and balloon/basket trawl alone, allowing clearance rates to exceed current guideline recommendations. Reference: 1 Wilkinson, et al . BSG ERCP – the way forward, A standards framework. 2014. http://www.bsg.org.uk Disclosure of Interest: None Declared